LEARNING SPATIAL AREAS BY DOCUMENTARY FILM PROJECT - R. Susty Sumiaty; Junaidi H. Matsum; Nuraini Asriati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
In millennial era, teacher should give something creative for their students. The creative things will make the students thinks something unique, and they can improve their knowledge. Technology and digital can give any benefit if the teacher using it in instructional process. In geography of Senior High School (SMA), the students learn about spatial areas. The problem in learning of spatial areas is some students couldn’t understand the kind of villages. Teacher can use problem solving method with give the students a project to make documentary film about spatial areas especially in village. Teacher let the students tell what kind of villages in their concept in documentary film. In Documentary film project, they will learn about many things, not only about spatial areas, but they will learn how to write the film concept, how to work together, how to using technology, and how to increase their sensitivities.